(untitled) (International Journal of Engineering and Computer Science, 2014)
The objective of this paper is to provide an algorithm to solve the problem that when all clients are relying on a single server. If that database becomes unavailable due to planned server downtime or from server failures, all of the remote workers will be disconnected from their data. Data is stored on their system (user system). When the user connected to the internet data automatically sink from their client system to the server in serial order. It also works on file handling. When the system is disconnected from network all the files(images) uploaded by user,saved on client machine folder when it is again connected with the server,automatically files(images) transferred from client to server.